Adoption and non-adoption of a shared electronic summary record in England: a mixed-method case study. (16th June 2010) - Greenhalgh, Trisha; Stramer, Katja; Bratan, Tanja; Byrne, Emma; Russell, Jill; Potts, Henry W W
Abstract : Objective To evaluate a national programme to develop and implement centrally stored electronic summaries of patients' medical records. Design Mixed-method, multilevel case study. Setting English National Health Service 2007-10. The summary care record (SCR) was introduced as part of the National Programme for Information Technology. This evaluation of the SCR considered it in the context of national policy and its frontline implementation and use in three districts. Participants and methods Quantitative data (cumulative records created nationally plus a dataset of 416 325 encounters in participating primary care out-of-hours and walk-in centres) were analysed statistically. Qualitative data (140 interviews including policy makers, managers, clinicians, and software suppliers; 2000 pages of ethnographic field notes including observation of 214 clinical consultations; and 3000 pages of documents) were analysed thematically and interpretively. Results Creating individual SCRs and supporting their adoption and use was a complex, technically challenging, and labour intensive process that occurred more slowly than planned. By early 2010, 1.5 million such records had been created. In participating primary care out-of-hours and walk-in centres, an SCR was accessed in 4% of all encounters and in 21% of encounters where one was available; these figures were rising in some but not all sites. The main determinant of SCR access was the identity of the clinician: individual clinicians accessed available SCRs between 0 and 84% of the time. When accessed, an SCR seemed to support better quality care and increase clinician confidence in some encounters. There was no direct evidence of improved safety, but findings were consistent with a rare but important positive impact on preventing medication errors. SCRs sometimes contained incomplete or inaccurate data, but clinicians drew judiciously on these data along with other sources. SCR use was not associated with shorter consultations or reduction in onward referral. Successful introduction of SCRs depended on interaction between multiple stakeholders from different worlds (clinical, political, technical, commercial) with different values, priorities, and ways of working. The programme's fortunes seemed to turn on the ability of change agents to bridge these different institutional worlds, align their conflicting logics, and mobilise implementation effort. Conclusions Benefits of centrally stored electronic summary records seem more subtle and contingent than many stakeholders anticipated, and clinicians may not access them. Complex interdependencies, inherent tensions, and high implementation workload should be expected when they are introduced on a national scale.